Measuring the costs and benefits of heart disease monitoring. Issue 6 (1st June 2000) - Perry, A; Capewell, S; Walker, A; Chalmers, J; Redpath, A; Major, K; Morrison, C E; Craig, N; Cobbe, S; Smith, W C S
Abstract : OBJECTIVE: To evaluate the costs and benefits of alternative systems of coronary heart disease monitoring in Scotland. DESIGN: An option appraisal was conducted to evaluate the costs and benefits of implementing a coronary heart disease monitoring system. This involved a review of existing Scottish datasets and relevant reports, specification of options, definition and weighting of benefit criteria by key stakeholders, assessment of options by experts, and costing of options. The options were assessed by 33 stakeholders (grouped as cardiologists, patient representatives, general practitioners, public health physicians, and policy makers), plus 13 topic experts. SETTING: Scotland (population 5.1 million). RESULTS: Between group mean benefit weights were: mortality rates and case fatality (10.6), quality of life (9.8), patient function (8.8), hospital activity (7.8), primary care activity (9.25), prescribing (5.72), socioeconomic impact (4.0), risk factors (7.4), prevalence (5.0), incidence (6.0), case registration (6.82), international comparability (4.2), breadth of coverage (8.8), and frequency (5.8). Differences between group weights were significant for prevalence (p = 0.048) and international comparability (p = 0.032). Four monitoring options were identified: a community epidemiology model, based on MONICA (monitoring trends and determinants in cardiovascular disease) study methodology applied to a series of eight representative communities, had the highest benefits, at an average annual discounted cost of approximately £360 000; models based on the Australian cardiovascular disease monitoring scheme and on enhanced routine data offered fewer benefits at discounted average annual costs ranging from £165 000 to £195 000; finally, a coronary heart disease registry modelled on the Scottish Cancer Registry scheme would have had fewer benefits and substantially higher costs than the other options. CONCLUSIONS: The most beneficial coronary heart disease monitoring system is the community epidemiology model, based on MONICA methodology. Option appraisal potentially offers an explicit and transparent methodology for evidence based policy development.